Expression of somatostatin receptor 2A in medullary thyroid carcinoma is associated with lymph node metastasis. Issue 10 (19th August 2016) - Herac, Merima; Niederle, Bruno; Raderer, Markus; Krebs, Michael; Kaserer, Klaus; Koperek, Oskar
Abstract : Medullary carcinoma (MTC) is an aggressive tumour that derives from the thyroid parafollicular calcitonin‐secreting cells (C cells). Lymph node metastasis may occur early in disease pathogenesis and is one of the most important negative prognostic parameters. Surgery is the only curative therapy while chemotherapeutic options are limited. Neuroendocrine differentiated C cells may express somatostatin receptors (SSTR), which have a wide range of biological actions including inhibitory effects on cell survival and angiogenesis and antiproliferative effects on cancer cell lines. Moreover, they are a potential target for various somatostatin analogues. Aim of this study was to analyse the protein expression of SSTR2A and 5 in MTCs with or without the presence of lymph node metastases in correlation with various clinicopathological parameters. This retrospective immunohistochemical analysis included 97 patients with medullary thyroid carcinomas. Protein expression was detected by immunohistochemistry for somatostatin receptors 2A and 5. Various clinicopathological parameters, such as Ki‐67 proliferation index or presence of desmoplasia, were included for statistical analysis. SSTR2A protein expression significantly correlated with the presence of lymph node metastases (p = 0.009), locally advanced MTCs staged according to the TNM (p < 0.001) and degree of desmoplasia (p = 0.029). Although SSTR5 protein expression significantly correlated with advanced stages of MTCs (p = 0.023) and degree of desmoplasia (p = 0.020), no correlation was found with the presence of lymph node metastases. Our results provide additional information concerning the aggressiveness of MTCs and reveal that a high SSTR2A and SSTR5 expression might be a poor prognostic feature.